2018
DOI: 10.1016/j.compositesa.2017.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Compression-After-Impact (CAI) strength of damage-tolerant hybrid unidirectional/woven carbon-fibre reinforced composite laminates

Abstract: The evaluation of Compression-After-Impact (CAI) strength is of great significance in the design of composite aerostructures. This paper presents a model for the numerical simulation of Compression-After-Impact (CAI) of hybrid unidirectional (UD)/woven carbon-fibre reinforced composite laminates. This three-dimensional damage model is based on Continuum Damage Mechanics (CDM) and Linear Elastic Fracture Mechanics (LEFM), and implemented as a user defined material subroutine (VUMAT) in Abaqus/Explicit. This mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(48 citation statements)
references
References 47 publications
2
44
0
Order By: Relevance
“…To calculate and compare the values of the contact pressures caused by the soft-gelatine projectiles and hard aluminium-alloy projectiles, the impact behaviour of the CF/PEEK composite target was modelled. The relevant material properties of the CF/PEEK composites required for the modelling studies may be found from the literature [11,12,15,[48][49][50][51][52][53][54] and are given in Table 4.…”
Section: Modelling Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…To calculate and compare the values of the contact pressures caused by the soft-gelatine projectiles and hard aluminium-alloy projectiles, the impact behaviour of the CF/PEEK composite target was modelled. The relevant material properties of the CF/PEEK composites required for the modelling studies may be found from the literature [11,12,15,[48][49][50][51][52][53][54] and are given in Table 4.…”
Section: Modelling Studiesmentioning
confidence: 99%
“…It can be seen that the aluminum-alloy impacted CF/PEEK composite exhibited a significantly higher reaction force than the gelatineimpacted CF/PEEK composite. The maximum reaction forces associated with the soft-gelatine Table 4 The input parameters for the composite damage model [11,12,15 Fig. 15 The FE model for simulating (a) the soft-gelatine particle (PC3D) impact and (b) the hard aluminiumalloy projectile impact on the composites and the hard aluminium-alloy impacts on the CF/PEEK composites were calculated to be 4.4 kN and 7.4 kN, respectively, see Fig.…”
Section: Modelling Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The failure modes, including delamination, fibre damage and matrix damage [21,23], which may occur in a woven composite ply are shown in Fig. 1a.…”
Section: Failure Modesmentioning
confidence: 99%
“…The air blast load on the sandwich panels was implemented as a time-dependent pressure using the tabular function in Abaqus. The general contact algorithm was used for global contact and a friction coefficient of 0.2 was used for the steel/composite contact surface (Falzon et al 2017;Liu et al 2018).…”
Section: Finite Element Modelmentioning
confidence: 99%